Photophysical and Chiroptical Properties of the Enantiomers of N, N'‐Bis(1‐phenylpropyl)‐2, 6‐pyridinecarboxamide and their Chiral 9‐Coordinate Ln3+ Complexes. Issue 40 (30th July 2020) - Chang, Victoria Y.; Calvinho, Karin U. D.; Tovar, Roberto C.; Johnson, Victoria A.; Straus, Daniel A.; Muller, Gilles
Abstract : The R, R and S, S enantiomers of N, N' ‐bis(1‐phenylpropyl)‐2, 6‐pyridinedicarboxamide, L(Et), react with Ln 3+ ions (Ln = La, Eu, Gd, and Tb) to give stable [Ln(( R, R )‐ and ( S, S )‐L(Et ))3 ] 3+ in anhydrous acetonitrile solution, as evidenced by various spectroscopic measurements, including NMR and luminescence titrations. In addition to the characteristic Eu 3+ and Tb 3+ luminescence bands, the steady‐state and time‐resolved luminescence spectra of the aforementioned complexes show the residual ligand‐centered emission of the 1 ππ* to 3 ππ* states, indicating an incomplete intersystem crossing (ISC) transfer from the 1 ππ* to 3 ππ* and ligand‐to‐Ln 3+ energy transfer, respectively. The high circularly polarized luminescence (CPL) activity of [Eu(L(Et) )3 ] 3+ confirms that using a single enantiomer of L(Et) induces the preferential formation of one chiral [Eu(L(Et) )3 ] 3+ complex, consistent with the [EuL 3 ] 3+ complexes formed with other ligands derived from a 2, 6‐pyridine dicarboxamide moiety. Furthermore, the CPL sign patterns of complexes with ( R, R ) or ( S, S ) enantiomer of L(Et) are consistent with the CPL sign pattern of related [LnL 3 ] 3+ complexes with the ( R, R ) or ( S, S ) enantiomer of the respective ligands in this family. Abstract : The enantiomers of L(Et), a ligand derived from the 2, 6‐pyridine dicarboxamide moiety, shows that its chiral [Ln(L(Et) )3 ] 3+ complexes preserve the favorable circularly polarized luminescence (CPL) activity with a CPL signal pattern consistent with the behavior of analogue Ln 3+ compounds with other structurally similar ligands, supporting further a relationship between structure and chiroptical properties.